2015
DOI: 10.1007/s11523-015-0388-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Survival Pathways MAPK and NF-kB Triggers Apoptosis in Pancreatic Ductal Adenocarcinoma Cells via Suppression of Autophagy

Abstract: Here we present evidence that allows us to consider a combined therapy regimen comprising an autophagy inhibitor and a MAPK or NF-kB pathway inhibitor as a possible treatment strategy for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 64 publications
0
46
0
Order By: Relevance
“…A previous study reported that the positive feedback loop between autophagy and the NF-κB signaling cascade might exacerbate the inflammation induced by H5N1 pseudotyped viral particles [28]. The inhibition of NF-κB was also documented to induce autophagy suppression, leading to apoptosis in pancreatic ductal adenocarcinoma cells [52]. We speculate that autophagy and inflammatory cascade reactions might be positively regulated by PEDV infection to exacerbate inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study reported that the positive feedback loop between autophagy and the NF-κB signaling cascade might exacerbate the inflammation induced by H5N1 pseudotyped viral particles [28]. The inhibition of NF-κB was also documented to induce autophagy suppression, leading to apoptosis in pancreatic ductal adenocarcinoma cells [52]. We speculate that autophagy and inflammatory cascade reactions might be positively regulated by PEDV infection to exacerbate inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…NF-κB is a transcription factor connected with several cellular processes such as inflammation, proliferation, apoptosis and development (Wang et al, 2008c; Meng et al, 2011; Sarode et al, 2015; Papademetrio et al, 2016). NF-κB comprises of five members, RelA (p65), RelB, c-Rel, p50, and p52 (Sun et al, 2013).…”
Section: Tgr5 and Cell Signalingmentioning
confidence: 99%
“…CAPE inhibits EMT in PaCa and is a potent apoptosisinducing agent (118). Its antiproliferative activity may involve the induction of mitochondrial dysfunction and the activation of caspase-3/caspase-7 (119). CAPE induces apoptosis after autophagy inhibition in a caspase-dependent and a caspase-independent manner in PaCa cells (120).…”
Section: Egcgmentioning
confidence: 99%